2014
DOI: 10.5152/tao.2014.584
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term, High-Frequency Tympanometry and Audiometry Results after Cartilage and Fascia Tympanoplasty

Abstract: Objective: Fascia or cartilage can be used as grafts in tympanoplasty; however, the disadvantage of cartilage is that it causes stiffness and rigidity in the newly formed tympanic membrane. The aim of this study was to compare the long-term high-frequency tympanometry and audiometry outcomes of tympanoplasty using cartilage and fascia.Methods: Forty patients in whom tragal cartilage was used in type 1 tympanoplasty and 40 patients in whom temporal muscle fascia was used were included in the study. The preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Cartilage graft was taken in 43 cases (97.7%) in this study, which is comparable to other studies as listed in table below (Table-III) [1][2][3]7,[10][11][12][13][14][15][16][17][18]. …”
supporting
confidence: 83%
See 2 more Smart Citations
“…Cartilage graft was taken in 43 cases (97.7%) in this study, which is comparable to other studies as listed in table below (Table-III) [1][2][3]7,[10][11][12][13][14][15][16][17][18]. …”
supporting
confidence: 83%
“…The commonly used autologous graft materials are vein, fat, fascia lata, temporalis fascia, tragal perichondrium and cartilages. 3 Temporalis facia and tragal perichondrium are most commonly used due to their anatomic proximity, compliance and translucency. To get closure of perforation and restore hearing caused by chronic suppurative otitis media, several trials were carried out since the 1600s.…”
Section: Introducionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also compared the middle ear pressure, air volume and compliance of tympanic membrane in both groups. They concluded that no statistical differences were observed in air volume, pressure or compliance values at any frequency in audiometry and tympanometry in the cartilage and fascia groups [22] . In our study, the graft take up rate in cartilage perichondria composite graft and temporalis fascia graft was 84.85% and 85% (statistically significant) respectively.…”
Section: Discussionmentioning
confidence: 94%